2013
DOI: 10.3390/rs5073476
|View full text |Cite
|
Sign up to set email alerts
|

Can Night-Time Light Data Identify Typologies of Urbanization? A Global Assessment of Successes and Failures

Abstract: Abstract:The world is rapidly urbanizing, but there is no single urbanization process. Rather, urban areas in different regions of the world are undergoing myriad types of transformation processes. The purpose of this paper is to examine how well data from DMSP/OLS nighttime lights (NTL) can identify different types of urbanization processes. Although data from DMSP/OLS NTL are increasingly used for the study of urban areas, to date there is no systematic assessment of how well these data identify different ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(81 citation statements)
references
References 37 publications
1
80
0
Order By: Relevance
“…In addition, the SNLD was frequently used to generate the urban area across different years [44,45]. However, the SNLD data has a blooming effect; the urban area extracted from SNLD was usually larger than the real urban area [44,47]. Figures 2c and 3c showed that the urban areas at WH extracted from SNLD contained the Yangtze River and some lakes, which should be removed in SUHI's study [3,10,48].…”
Section: Extraction Of Urban Areamentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the SNLD was frequently used to generate the urban area across different years [44,45]. However, the SNLD data has a blooming effect; the urban area extracted from SNLD was usually larger than the real urban area [44,47]. Figures 2c and 3c showed that the urban areas at WH extracted from SNLD contained the Yangtze River and some lakes, which should be removed in SUHI's study [3,10,48].…”
Section: Extraction Of Urban Areamentioning
confidence: 99%
“…2017, 9, 540 5 of 17 was usually larger than the real urban area [44,47]. Figures 2c and 3c showed that the urban areas at WH extracted from SNLD contained the Yangtze River and some lakes, which should be removed in SUHI's study [3,10,48].…”
Section: Extraction Of Urban Areamentioning
confidence: 99%
“…Finally, substantial quantities of impervious surfaces can exist within rural areas, including rural roads, highways, and farmhouses, which might not all be well lit and thus can be missed by the NDUI (Figure 14). Some urban areas are in darkness due to the lack of electricity and humanitarian disasters [63][64][65] and non-urban bare land can be influenced by night lights, which will also lead to underestimation or overestimation accordingly.…”
Section: Discussionmentioning
confidence: 99%
“…While lights appear in rural human settlements, which are altered landscapes that are less urban; there is a higher brightness factor in urban areas (Figure 2). DMSP OLS data more accurately identify urbanization in developed countries, but are less accurate in developing countries [14]. One challenge in mapping the urban extent is misclassification between urban and non-urban surfaces.…”
Section: Urban Extentmentioning
confidence: 99%